2020
DOI: 10.1088/1742-6596/1515/4/042051
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing the spray angle of the irrigation device on the spray diameter

Abstract: The paper is devoted to the research in the field of the effective application of the main working elements of sprinkler machines showing the influence of their basic capabilities on each other. The aim of the study was to develop and improve the performance of irrigation systems for the possibility of irrigation process optimization. As a result, it was found that the ratio between the spray angle and its maximum height at different pressures is equivalent to the second-order parabola equation. The inferred e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, a search is made for the angle of inclination of the water jet, which will give a larger radius. An increase in the spray radius can increase the distance between the sprinklers, which is desirable for the irrigator (Antypas et al, 2020), as it reduces the number of sprinklers needed in the area.…”
Section: Angle Of Inclination Of the Water Jetmentioning
confidence: 99%
“…Therefore, a search is made for the angle of inclination of the water jet, which will give a larger radius. An increase in the spray radius can increase the distance between the sprinklers, which is desirable for the irrigator (Antypas et al, 2020), as it reduces the number of sprinklers needed in the area.…”
Section: Angle Of Inclination Of the Water Jetmentioning
confidence: 99%
“…The main function of threshing is disruption of the link between a grain and an ear, but this link depends on various factors such as grain mass humidity at the moment of harvesting, ear texture, maturity, and dimensions. This research was conducted in a lab environment using specially designed laboratory machines and on-farm using experimental units [1].In the context of disruption of the link between a grain and an ear, it was found that multiple stress on grain mass disrupts the link between a grain and an ear. Separation of a grain and an ear rises with an increase in impact frequency, but at high speeds [3] there is a reduction [4] in the quality of a grain and excessive grain shattering [5].…”
Section: Introductionmentioning
confidence: 99%